Development of Interactive Multimedia for Physics Learning on Electromagnetic Induction Material to Improve Concept Mastery - Mintarsih, Mintarsih; Harbani, Arif (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2024)
The majority of students have not mastered the concepts of physics which is the background for this research to be carried out. The research aims to produce interactive multimedia for physics learning on electromagnetic induction material and analyze the effectiveness of this product in increasing concept mastery. The research method is Research and Development, followed by pre-experimental research. The development procedure was adapted from Sukmadinata model with three steps: preliminary study, product development, and product test. Data collection strategy using assessment sheets and pretest-posttest. The validation of interactive multimedia as shown by the research results is 95.15%, including the very good category. Classical learning completeness of 94% meets the criteria to be achieved in the research. The conclusion from these results is that interactive multimedia for physics learning on electromagnetic induction material is very good and effective for increasing concept mastery.